Perceived credibility and consumption of homeland news among diasporic Nigerians in Malaysia - Mustapha, Lambe Kayode; Wok, Saodah (2014)
The increasing migration, powered by advanced transportation, information and communication technologies, has created huge diasporic communities around the globe. Through push and pull forces, citizens of countries across the world have migrated from their homelands to near and far locations in search of better socio-political and economic opportunities and possibilities. In their new milieu, this corps of transnational migrants maintained close attachment with their countries of origin via a plethora of cyber-powered homeland communication and media artifacts. The migration of homeland traditional print and electronic media to the Internet, however, offers news avenues for migrants’ consumption of unadulterated news about events happening in their countries. While migrants’ homeland media consumption has received tremendous attentions among scholars, little concern has been accorded factors that predict the forms and types of homeland media attracting migrants’ attention. This study explores the relationship between perceived credibility and consumption of news from the online newspapers among Nigerian students in Malaysia (N=321). Findings reveal differential perceptions of three Nigerian online newspapers in terms of story depth, fairness, accuracy and trustworthiness. Similarly, perceived credibility of each online newspaper relates to reading the newspapers the most among the respondents. The study thus offers practical implications of perceived credibility of homeland newspapers for increased readership among diasporic audience who could be valuable patrons of and contributors to homeland journalistic products.